Celebrities’ Role in the Conflict Resolution Processes: George Clooney in South Sudan - Ženková Rudincová, Kateřina (Modern Africa: Politics, History and Society, 2020)
The present article discusses the role of celebrities in the conflict resolution processes presented by the case study of George Clooney’s engagement in South Sudan. Methodologically, it is a critical discourse analysis of published articles in selected media. The main argument of the article is that the role of celebrities in conflict resolution processes is overestimated by media and the image of celebrities’ involvement reproduces stereotyped understanding of distant regions as lacking agency and dependent on the actors from the West. The image of Clooney’s role in the South Sudanese peace process creates an idea that celebrities have been crucial actors in this process. The present article brings critical new insights on the engagement of celebrities, including the fight against the violation of human rights and points out the corruption of South Sudanese politicians.